الاستثمار في الطاقات المتجددة و متطلبات تحقيق الأمن الطاقوي:الاستفادة من التجربة الأمريكية و الإشارة لحالة الجزائر. - رحايلية, سيف الدين; بوداح, عبد الجليل (Recherches économiques et managériales; Vol. 21 (2017): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES, 2018)
تعتبر قضية الأمن الطاقوي من ضمن القضايا الأساسية التي تشغل الرأي العام العالمي خصوصا في ظل تزايد الطلب على الطاقة الموجهة لدواعي التنمية الاقتصادية . من جهة أخرى، فإن اعتماد العالم على مصادر طاقوية ناضبة لم يعد كافيا لإشباع الطلب المتزايد على الطاقة، لذا نلاحظ مجهودات دولية للتنويع الطاقوي و الاستثمار فيما يعرف بالطاقات المتجددة . و من بين الدول الرائدة في هذا المجال نجد الولايات المتحدة، التي يمكن أن تكون محلا للاستفادة من تجربتها الخاصة و تطبيقها على بلد كالجزائر . فالاختلاف البين بين المنظومة الاقتصادية للجزائر و بلد كالولايات المتحدة الأمريكية قد يجعل إستراتيجية الجزائر نحو تحقيق الأمن الطاقوي تؤسس على دعائم مختلفة مقارنة بالولايات المتحدة الأمريكية، وهذا ما تسعى إليه هذه الورقة البحثية لإبراز الآليات الأكثر انسجاما مع أهداف البلد استراتيجيا، ودون تفويت فرصة الأخذ بتجارب الآخرين في هذا المجال . الكلمات المفتاحية : الطاقات المتجددة، الأمن الطاقوي، الاستثمار، الطاقة في الجزائر، الطاقة في الولايات المتحدة . Abstract The issue of energy Security is becoming a very crucial problem within the world wide opinion, especially in view of the increasing demand for energy directed at economic development . On the other hand, the world's dependence on depleted energy sources is no longer sufficient to meet the increasing demand for energy. Therefore, we note international efforts to diversify energy and investment in renewable energies. Among the leading countries in this field, we find the United States, which can be a place to take advantage of its own experience and applied to a country such as Algeria, The difference between the economic system of Algeria and the United States of America may make Algeria's strategy towards achieving energy security based on different pillars compared to the United States of America, This paper seeks to highlight the mechanisms most in line with Algeria's strategic objectives, without missing the opportunity to introduce the experiences of other countries in this field. Mots-clés: Renewable energies, the energy security, investment, energy in Algeria, the energy in the United States.